Proceedings of the Fortieth Annual ACM Symposium on Theory of Computing 2008
DOI: 10.1145/1374376.1374384
|View full text |Cite
|
Sign up to set email alerts
|

Algorithms for subset selection in linear regression

Abstract: We study the problem of selecting a subset of k random variables to observe that will yield the best linear prediction of another variable of interest, given the pairwise correlations between the observation variables and the predictor variable. Under approximation preserving reductions, this problem is also equivalent to the "sparse approximation" problem of approximating signals concisely.We propose and analyze exact and approximation algorithms for several special cases of practical interest. We give an FPT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
158
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 162 publications
(173 citation statements)
references
References 36 publications
1
158
0
3
Order By: Relevance
“…defined above is submodular (Das and Kempe, 2008;Krause et al, 2008a), we found empirically that in our case ρ(·) is not quite submodular (see section 4.4 for details). Nevertheless, the greedy algorithm (and the lazy implementation) proved to be quite effective in practice, as we will see below.…”
Section: Selecting Observation Locations Via Submodular Optimization mentioning
confidence: 45%
See 2 more Smart Citations
“…defined above is submodular (Das and Kempe, 2008;Krause et al, 2008a), we found empirically that in our case ρ(·) is not quite submodular (see section 4.4 for details). Nevertheless, the greedy algorithm (and the lazy implementation) proved to be quite effective in practice, as we will see below.…”
Section: Selecting Observation Locations Via Submodular Optimization mentioning
confidence: 45%
“…Selecting the optimal set of observations O is NP-hard in general (Das and Kempe, 2008;Krause et al, 2008a), and therefore we must rely on approximate methods to design an optimal sampling scheme. There is a significant body of work on maximizing objective functions that are submodular (see, e.g., (Krause et al, 2008b) and references therein).…”
Section: Selecting Observation Locations Via Submodular Optimization mentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past year, we have obtained the following key results (which are currently under submission [1] The quality of approximation is characterized precisely in [1], but omitted here due to space constraints. This result improves on the ones of [6,17], in that it analyzes a more commonly used algorithm, and obtains somewhat improved bounds.…”
Section: A Mathematical Formulation Of Sample Selectionmentioning
confidence: 99%
“…Hence, we also study the case of sensors embedded in a metric space, where the covariance between sensors' readings is a monotone decreasing function of their distance. The general version of this problem is the subject of ongoing work, but [1] contains a promising initial finding:…”
Section: Theorem 2 If the Pairs Of Variables X I With High Covariancmentioning
confidence: 99%